Fiscal policy adjustments in the euro area stressed countries: new evidence from non-linear models with state-varying thresholds - Roberto A. De Santis; Gabriella Legrenzi; Costas Milas (European Central Bank (ECB), 2015)
We introduce a non-linear model to study the adjustment of fiscal policy variables in Greece, Ireland, Portugal and Spain over the last 50 years, based on endogenously estimated budget deficit-to-GDP thresholds, which vary with fiscal disequilibria, the economic cycle and financial market conditions. We find that the budget deficit-to-GDP thresholds were rather high for Greece and Portugal particularly after 1999 and that the fiscal adjustments in "good" times were very different from the adjustments that took place in "bad" times. We also found that only in Spain fiscal deficits were reduced in expansionary times. Finally, we provide evidence that, under financial market pressure, fiscal authorities relaxed the fiscal deficit-to-GDP threshold for the adjustment in Ireland and Spain and reduced such threshold for the adjustment in Portugal.
Keywords: H63; H20; H60; C22; 330; budgetary disequilibria; euro periphery; European debt crisis; fiscal adjustments; non-linear models